Serological detection of West Nile virus in horses and chicken from Pantanal, Brazil - Melandri, Vanessa; Guimarães, Anthony Érico; Komar, Nicholas; Nogueira, Maurício L; Mondini, Adriano [UNESP]; Fernandez-Sesma, Ana; Alencar, Jeronimo; Bosch, Irene (Instituto Oswaldo Cruz, Ministério da Saúde, 2012)
In an effort to detect West Nile virus (WNV) in Brazil, we sampled serum from horses and chickens from the Pantanal region of the state of Mato Grosso and tested for flavivirus-reactive antibodies by blocking ELISA. The positive samples were further confirmed for serological evidence of WNV infection in three (8%) of the 38 horses and one (3.2%) of the 31 chickens using an 80% plaque-reduction neutralisation test (PRNT80). These results provide evidence of the circulation of WNV in chickens and horses in Pantanal.
Keywords: WNV; b-ELISA; PRNT; Brazil